Influence of Extreme Ultraviolet Irradiance Variations on the Precipitating Ion Flux From MAVEN Observations. Issue 13 (6th July 2019) - Martinez, A.; Leblanc, F.; Chaufray, J. Y.; Modolo, R.; Witasse, O.; Dong, Y.; Hara, T.; Halekas, J.; Lillis, R.; McFadden, J.; Eparvier, F.; Leclercq, L.; et al.
Abstract: We study the influence of the solar extreme ultraviolet (EUV) flux intensity on the precipitating ion fluxes as seen by the Solar Wind Ion Analyzer, an energy and angular ion spectrometer aboard the Mars Atmosphere and Volatile EvolutioN (MAVEN) spacecraft. We defined three periods with significantly different EUV flux intensity (1.6 and 3.2 times the lowest EUV intensity) and compare the precipitating ion flux measured by MAVEN/Solar Wind Ion Analyzer during each period. At low energy [30–650] eV, we find that the median (average) precipitating ion flux during the medium and low EUV periods are, respectively, 1.7 (2.1) and 3 (3.5) times more intense than the flux during the high EUV period. At high energy [650–25, 000] eV, a similar trend in the intensity of the precipitating ion flux is observed but with an increase by 50% (46%) and 70% (79%), respectively. A larger EUV flux does therefore not seem to favor heavy ion precipitation into Mars's atmosphere, contrary to modeling prediction and overall expectations. Key Points: Under similar solar wind conditions, the increase of the EUV/UV flux intensity is associated with a decrease of the precipitating ion flux This decrease is more important at low ion energy [30–650] eV than at high ion energy [650–25, 000] eV Theses results are in contradiction with previous theoretical studies